Framing the social art of influence - Klintman, Mikael 1968- (Manchester University Press, 2025)
A toolkit for understanding how the framing of information influences the way we see the world. Combining insights from the social sciences, economics and evolutionary biology, Klintman lays out a four-part approach to understanding how information is 'framed' for us, built around the key elements of texture, temperature, position and size